SAIBERKOM UNTUK PENINGKATAN HOTS DAN HASIL BELAJAR IPA PADA SISWA KELAS IV - Rujiani Rujiani (Universitas PGRI Yogyakarta, 2019)
AbstractHigh-level thinking skills have become demands from the Curriculum section of 2013, in addition to increasing students' understanding in various learning content. Less conducive learning atmosphere, so that influences the low HOTS and student learning outcomes, then comic-assisted scientific collaboration (saiberkom) to overcome the problem. This study uses a class action research design, carried out in two cycles in which there are four main stages of activity, namely planning, action, observation, and reflection. In this action research uses data from tests, observations, journals, interviews, documentation, and using descriptive analysis. The results of the study in the first cycle showed an increase in HOTS and student learning completeness from 30% on pre-cycle to 60%. In cycle II HOTS increased to 80% and student learning completeness reached 90%. From these results, it was concluded that HOTS and the quality of fourth grade students had increased with the presence of telecoms.Keywords: scientific, comic, HOTS, learning outcomes, and the nature of scienceÂ